Сказки - Пушкин Александр Сергеевич (Мои любимые стихи, 2007)
Экземпляры: ф-21 (ретроконверсия) / Инвентарный номер: 42760 / Цена: 94.00 / Сис.шифр: Р1 / Авт.знак: П 91 / ГРНТИ: 17.82 / ББК: 84(2=411.2)1